2008
DOI: 10.1093/jxb/ern007
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle trafficking dynamics and visualization of zones of exocytosis and endocytosis in tobacco pollen tubes

Abstract: Pollen tubes are one of the fastest growing eukaryotic cells. Rapid anisotropic growth is supported by highly active exocytosis and endocytosis at the plasma membrane, but the subcellular localization of these sites is unknown. To understand molecular processes involved in pollen tube growth, it is crucial to identify the sites of vesicle localization and trafficking. This report presents novel strategies to identify exocytic and endocytic vesicles and to visualize vesicle trafficking dynamics, using pulse-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
188
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(201 citation statements)
references
References 59 publications
(87 reference statements)
12
188
0
1
Order By: Relevance
“…Fayant et al, 2010) measurements that probe the local properties of the wall with quantitative measurement on the local rate of exocytosis (see e.g. Zonia and Munnik, 2008) may serve to validate some of the ideas presented here.…”
Section: Discussion and Outlookmentioning
confidence: 76%
See 1 more Smart Citation
“…Fayant et al, 2010) measurements that probe the local properties of the wall with quantitative measurement on the local rate of exocytosis (see e.g. Zonia and Munnik, 2008) may serve to validate some of the ideas presented here.…”
Section: Discussion and Outlookmentioning
confidence: 76%
“…the apical region, than areas farther away along the tube. Finally, it should be mentioned that there is strong experimental evidence that in several tip-growing cells the maximum rate of vesicle delivery is not at the apex, but rather at an annular region just downstream from the apex (Bove et al, 2008;Zonia and Munnik, 2008). This could in principle be modelled by a non-monotonic supply factor, with a maximum at an apex distance s max > 0, but we chose to forego these additional complexities here.…”
Section: Supply Factormentioning
confidence: 99%
“…For 120K to arrive at a vacuole, it must travel from the ECM through the pollen tube endomembrane system. Recent work has highlighted two distinct endocytic pathways in pollen tubes (54,55). Both clathrin-coated and noncoated vesicle endocytic pathways exist; clathrincoated vesicles traffic to the trans-Golgi, whereas noncoated vesicles travel to the multivescular body and a vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PME data in tobacco challenge this view by showing that the inverted cone stains much less brightly than the flanks surrounding the cone ; data herein). It is possible that material moves forward along the edge of the cell, being directed by the cortical actin fringe (Lovy-Wheeler et al, 2005), and deposits as an annulus outside of the polar axis (Bove et al, 2008;Zonia and Munnik, 2008), as has been shown for root hairs (Shaw et al, 2000;Dumais et al, 2004). This is an attractive idea, but more work is needed to establish its occurrence in pollen tubes.…”
Section: Exocytosis Has Been Studied In Other Pollen Tubesmentioning
confidence: 97%